Representations of Ageing in Contemporary Zimbabwe: A Gerontological Reading of NoViolet Bulawayo’s (2013) We Need New Names - Chipo Hungwe; Elda Hungwe; Zvenyika Eckson Mugari (Springer, 2023)
While many studies have interrogated the novel We Need New Names, on topics such as citizenship, migration, and transnationalism, there is still much more that readers can learn through interrogating the author’s depiction of older adults’ experiences of ageing in place, ageism, healthy ageing and intergenerational relationships in Post-colonial Zimbabwe. It is argued that in so far as ageing is concerned, the novel presents a very grim picture of older adults caught up and responding to the circumstances of a country in the throes of a deep social, political and economic crisis. Urban poverty is portrayed as a real challenge affecting Zimbabweans and so are the weak social bonds that connect the younger and older generations. Social gerontologists stand to benefit from studying this novel which clearly depicts the challenges of migration, urban renewal and development projects, and poverty on the most vulnerable of all populations - the older adults. The novel portrays the Zimbabwean economic crisis as not just an isolated phenomenon, but one of the processes of globalization, which creates opportunities, and improves people’s lives while at the same time destabilizing the lives of older adults by not only severing connections with the younger generations but also with the departed ancestors in the hereafter. The novel provides an important contribution to our understanding of ageing issues in Zimbabwe as it goes against the grain by giving voice and space to older adults who are often ignored by mainstream media.